Utilization of Information Technology and the Effectiveness of BPJS Employment Services in Indonesia - Jasni Widyanto; Nadhila (Mustard Journal De Ecobusin, 2025)
The article examines the impact of information technology (IT) application on the effectiveness of services in BPJS BPJS Employment, which is an important institution of public significance serving as an employment social security provider in Indonesia. The quantitative method was used to collect data using questionnaires adapted in a structured design that targeted 120 respondents most of whom were a combination of staff and service users. The product of an inferential statistical procedure such as correlation and linear regression data results, showed that there is a positive correlation between IT utilization and service effectiveness, which was strong and significant. Regression model indicated that IT usage was related to 55.1 percent of the variation in service effectiveness due to the standardized coefficient of 0.742 and the p-value of <0.001. The results of the study show that online registration, automated claims, and mobile platforms increase the value and efficiency of services and have a considerable influence on their manifold dimensions of quality, velocity, and accuracy. The research will fill this gap in a literature base by providing an empirical evaluation of the e-governance processes in Indonesia; it fills this gap because it will provide a quantitative analysis of e-governance processes in Indonesia in a context where most of the literature only presents the qualitative perspectives of the e-governance processes. The findings emphasize the strategic essence of enhancing IT infrastructure, training of these users and digital literacy in the quest to enhance further provision of the services in the institutions in the public sector.